2011
DOI: 10.1063/1.3573999
|View full text |Cite
|
Sign up to set email alerts
|

Microspectroscopy of ultrafast laser inscribed channel waveguides in Yb:tungstate crystals

Abstract: We report microspectroscopy measurements of crystalline channel waveguides fabricated in Yb: KGd͑WO 4 ͒ 2 and Yb: KY͑WO 4 ͒ 2 using the ultrafast laser inscription technique. From these measurements we find that densification of the WO 2 W bridge in the double tungstate crystal lattice is responsible for the refractive index increase, which creates the waveguide confinement. We identified that shifts toward lower energies in the ϳ760 cm −1 Raman mode indicate regions, which guide light polarized along the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Bain et al. fabricated Type II waveguides in both Yb:KYW and Yb:KGW . The reported propagation loss was 3.9 dB/cm and 1.9 dB/cm for KYW and KGW waveguides, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Bain et al. fabricated Type II waveguides in both Yb:KYW and Yb:KGW . The reported propagation loss was 3.9 dB/cm and 1.9 dB/cm for KYW and KGW waveguides, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The pump source was a single-mode fiber-coupled 980 nm InGaAs laser diode. Later, the same authors reported on micro-Raman spectroscopy of such waveguides by monitoring several characteristic Raman bands [103]. The authors concluded that the densification of the double-oxygen WOOW bridges in the lattice is responsible for the refractive index change around the irradiated regions.…”
Section: Fs-dlw Double Tungstate Waveguide Lasersmentioning
confidence: 97%
“…In the last years, much effort has been done to retrieve the strain and refractive index field using different simulations and measurements. As a result, residual strain was determined as a relevant cause of wave guiding formation [4] and l-Raman and l-luminescence maps were widely employed to analyse femtosecond laserwritten structures [5][6][7][8][9][10]. In particular, iterative approaches using an elastic and numerical model were employed to compute the residual strain and the refractive index field [11].…”
Section: Introductionmentioning
confidence: 99%